Diquat Based Dyes: A New Class of Photoredox Catalysts and Their Use in Aerobic Thiocyanation. Issue 22 (8th March 2023) - Meier, Armin; Badalov, Sabuhi V.; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René
Abstract: A series of new organic donor–π–acceptor dyes incorporating a diquat moiety as a novel electron‐acceptor unit have been synthesized and characterized. The analytical data were supported by DFT calculations. These dyes were explored in the aerobic thiocyanation of indoles and pyrroles. Here they showed a high photocatalytic activity under visible light, giving isolated yields of up to 97 %. In addition, the photocatalytic activity of standalone diquat and methyl viologen through formation of an electron donor acceptor complex is presented. Abstract : From diquat to dye‐cat . A series of push–pull dyes using diquat as the electron‐acceptor moiety have been synthesized. Their photocatalytic abilities were tested in the aerobic thiocyanation of indoles and pyrroles, giving yields of up to 97 %.